2016
DOI: 10.1111/jpn.12457
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lemon verbena powder and vitamin C on performance and immunity of heat‐stressed broilers

Abstract: An experiment was conducted to investigate the effect of lemon verbena powder and vitamin C on performance and immunity of broilers under heat stress. The experiment was carried out with a total of 160-day-old male Ross 308 broiler chickens in a completely randomized design. From 25 days of age, the birds were assigned to four diets including control diet and treatment diets which were supplemented with 2 levels of lemon verbena (0.5% and 1.0%) and one level of vitamin C (250 mg/kg) in 16-floor pens with 10 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 25 publications
0
17
0
3
Order By: Relevance
“…37 Lemon verbena and vitamin C improved some performance data and blood metabolites which somehow suppressed the negative effects of heat stress. 38 In our current research, add PAMK also could improve the immune functions, it showed that PAMK had the similar function as the above phytochemicals.…”
Section: Discussionmentioning
confidence: 54%
“…37 Lemon verbena and vitamin C improved some performance data and blood metabolites which somehow suppressed the negative effects of heat stress. 38 In our current research, add PAMK also could improve the immune functions, it showed that PAMK had the similar function as the above phytochemicals.…”
Section: Discussionmentioning
confidence: 54%
“…As a result of various adverse effects on performance, health, and even the animal's welfare, many researchers have reported that dietary supplementation strategy is an effective and feasible approach to alleviate the negative effects of heat stress in poultry. Interestingly, the positive effects of supplementation of vitamins, mineral, amino acids, and phytochemicals have been observed (Liu et al., ; Panda, Ramarao, Raju, & Chatterjee, ; Rafiee, Mazhari, Ghoreishi, & Esmaeilipour, ; Xu & Tian, ). Phytochemicals, which are bioactive compounds of plants, have been shown beneficial for performance and health of poultry under heat stress.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, dietary supplementation with Vc has been shown to be beneficial for the reduction of stress in livestock (Imik et al, 2012;Mahmoud, Edens, Eisen, & Havenstein, 2003;Sahin et al, 2009;Sahin, Onderci, Sahin, Gursu, & Smith, 2004;Szczubial, 2015). Supplementation with Vc can also mitigate heat-related damage and enhance heat resistance in animals (Jang, Ko, Moon, & Sohn, 2014;Panda et al, 2008;Rafiee, Mazhari, Ghoreishi, & Esmaeilipour, 2016;Redmond et al, 2010). In male reproductive system, Vc is an essential micronutrient for the development of male germ cells (Altoe, Reis, Gomes, Dolder, & Priovani, 2017;Angulo et al, 2011), Angulo et al (2008) found that Sertoli cells express Vc functional transport systems, which can participate directly in Vc transport throughout the BTB.…”
Section: Introductionmentioning
confidence: 99%